Effect of medicinal plants on wound healing. Issue 2 (March 2015) - Budovsky, Arie; Yarmolinsky, Ludmila; Ben‐Shabat, Shimon
ABSTRACT In the United States alone, chronic wounds affect 6.5 million patients. It is expected that the number of chronic wounds will increase worldwide due to the increase in age‐related conditions and pathologies such as diabetes, obesity, and cardiovascular diseases. An estimated excess of US$25 billion is spent annually on treatment of chronic wounds, and the burden is rapidly growing due to increasing healthcare costs, an aging population, and a sharp rise in the incidence of diabetes and obesity worldwide. While current therapeutic agents have generally inadequate efficacy and number of serious adverse effects, the medicinal plants have been used in medicine since ancient times and are well known for their abilities to promote wound healing and prevent infection without grave side effects. Thus, herbal therapy may be an alternative strategy for treatment of wounds. The purpose of this review is to provide the verified data on the medicinal plants of the world flora with wound healing activity including the biologically active substances belonging to these herbal preparations and describe in detail the various cellular and molecular mechanisms of their actions.